Contemporary Agreement Law Discusing Electronic Agreements In Electronic Media Transactions On The Aspect Of Their Legitimacy - Nurharsya Khaer Hanafie; Herman Herman; Andika W Gani; Firmansyah Firmansyah (Seminar Nasional LP2M UNM, 2022)
Abstract. This study analyzes the validity of the electronic agreement. The purpose of this study specifically will dissect and analyze aspects of the agreement in the Civil Code and explore the legality of electronic agreements in the practice of electronic media transactions. The research method used is normative juridical research, because in parsing and discussing the use of applicable regulatory instruments along with library materials as primary sources in research, the research approach is by taking a statutory approach, by looking at the phenomenon of technological developments, it is also necessary to look at the regulatory instruments by analyzing regulations related to contract law according to positive law as the foundation in conducting electronic agreement practices. This research is a descriptive research, which aims to explain how legal certainty is to the practice of electronic agreements used by technology users in conducting virtual contractual transactions. Based on the results of the study, it can be concluded that the electronic agreement already has adequate legal instruments. 19 of 2016 concerning information and electronic transactions. Therefore, the legal structure used to make electronic agreements can be applied in Indonesia, although in the author's opinion, there are still some regulatory improvements in the midst of the development of virtual transactions in order to provide legal certainty to the public. Keywords: Electronic Agreement, Legal Agreement, Electronic Media Transactions.